Can flexible pavements' waste (RAP) be utilized in cement concrete pavements? – A critical review. (30th October 2020) - Debbarma, Solomon; Selvam, M.; Singh, Surender
Highlights: Coarse RAP holds better potential than fine RAP for concrete pavements. Asphalt film and agglomerated particles reduces the suitability of RAP. Asphalt cohesion failure is associated with RAP-concrete. Coarse RAP upto 50% could produce a durable concrete matrix. Surface treatment is better than adding admixtures for enhanced performance. Abstract: Recycling of flexible pavement leads to the accumulation of an enormous quantity of Reclaimed Asphalt Pavement (RAP) aggregates which are generally dumped legally/illegally in the nearby vicinities causing several challenges to the agencies. Utilization of these aggregates in cement concrete pavements seem to be a novelistic approach and could facilitate with many socio-economic-environmental benefits. However, its inclusions may negatively affect structural and functional performance as well. Therefore, this paper presents an extensive and critical review of the suitability of RAP for the production of concrete mixes along with identifying the various gaps that need to be bridged to induce sustainability in pavements. The schematic flow of this paper is as follows: firstly, the RAP aggregates were characterized, followed by the fresh state RAP-concrete properties, and lastly, the mechanical and durability properties were investigated. The literature review depicted that the RAP aggregates are inferior to natural aggregates but it may not be a big concern from the point of fresh state properties. The presence of asphalt film and agglomerated particles in RAP were noted to be the primary factors responsible for the reduction in the overall strength properties; however, coarse and fine RAP (individually) up to 50% could be utilized since the minimum strength benchmarks could be met. In terms of durability, coarse RAP up to 50% may provide adequate chloride-ion penetration resistance and freeze–thaw durability. Benefits such as enhanced toughness and workability were positively identified by the incorporation of RAP, whereas, porous microstructure could be expected, which may provide passage to aggressive ions from nearby environments resulting in significant deterioration of the concrete. Including supplementary cementitious admixtures could not improve the mechanical performance due to the asphalt cohesion failure associated with these hybrid mixes, but durability performance could be enhanced slightly. On the other hand, surface treatment methods could improve the bonding potential between RAP and mortar paste. This review is expected to address several key issues on the utilization of RAP in cement concrete pavements and encourages academicians and highway agencies to form a framework for effective utilization of RAP for sustainable pavement systems.